The VALUES OF PEACE EDUCATION IN YALAHATAN COMMUNITY, CENTRAL MALUKU - Hamka, Syamsuar; Umarella, Samad (al-Iltizam: Jurnal Pendidikan Agama Islam, 2024)
Conflict is a prevalent issue in Indonesia. The spread of ideologies that threaten cultural existence stems from seeds leading to physical violence and a 'culture of war'. Therefore, there is a need for studies on peace education derived from the culture of the community itself, such as in the Dusun Yalahatan community. This community exhibits unique characteristics compared to other villages, where multiple family members within a single household may adhere to different religions, yet they practice mutual tolerance. This pluralistic society is maintained within their social life. The objective of this research is to examine the implementation of peace education values within the Dusun Yalahatan community. This study employs a qualitative approach, with the subjects being members of the Dusun Yalahatan community. Data collection techniques include observation, interviews, and documentation, while data analysis is conducted through data reduction, data presentation, and conclusion drawing. The research findings indicate that the peace education values within the Dusun Yalahatan community include respect for others, gender equality, cooperation, as well as openness and tolerance.